2012
DOI: 10.1152/ajpheart.00321.2012
|View full text |Cite
|
Sign up to set email alerts
|

Focal but reversible diastolic sheet dysfunction reflects regional calcium mishandling in dystrophicmdxmouse hearts

Abstract: Cardiac dysfunction is a primary cause of patient mortality in Duchenne muscular dystrophy, potentially related to elevated cytosolic calcium. However, the regional versus global functional consequences of cellular calcium mishandling have not been defined in the whole heart. Here we sought for the first time to elucidate potential regional dependencies between calcium mishandling and myocardial fiber/sheet function as a manifestation of dystrophin-deficient ( mdx) cardiomyopathy. Isolated-perfused hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 81 publications
(112 reference statements)
6
23
0
Order By: Relevance
“…The directional DTI parameters shown in Figs. and are consistent with previous cardiac DTI studies . Compared with D120, the HA distribution in the LV of 5 m significantly shifted toward circumferential orientation (17% increase) at the expense of significant reduction of LHF (by 44%) (Table ), while the HA slope decreased by 28% only in the RV (Table ).…”
Section: Resultssupporting
confidence: 89%
“…The directional DTI parameters shown in Figs. and are consistent with previous cardiac DTI studies . Compared with D120, the HA distribution in the LV of 5 m significantly shifted toward circumferential orientation (17% increase) at the expense of significant reduction of LHF (by 44%) (Table ), while the HA slope decreased by 28% only in the RV (Table ).…”
Section: Resultssupporting
confidence: 89%
“…Potentially, the increased dilation of ttubules on the order of ∼150 nm could lead to structural remodelling of the cellular cytoskeleton, leading to the displacement of LTTC and RyR in cardiac junctions on the order of 10-20 nm required to disrupt Ca 2+ release. Consistent with this proposal, the MDX mouse that has no dystrophin has disrupted cellular cytoskeleton (Viola et al 2014) and disrupted calcium release (Cheng et al 2012). In addition, the vinculin-talin-integrin system could likely have a role in t-tubule remodelling, given its linkage to the actin cytoskeleton (Ziegler et al 2008) and the promiscuity of integrin (depending on the receptor sub-type) to bind to different ECM components, including laminin, fibronectin and collagens, including types I, III, IV and VI (Ross and Borg 2001;Tulla et al 2001), which have all been shown to be within the t-tubules (Kostin et al 1998;Crossman et al 2017).…”
Section: Collagens and Nanoscale T-tubule Remodellingmentioning
confidence: 68%
“…Therefore the significantly different slope in fiber orientation changes over the depth cannot be caused by any differences in the wall thickness. It is important to note that this study only measured the helix angle of the 3D myocardial fiber located within the plane perpendicular to the incident light [2,8]. Therefore, any orientation changes in planes that are parallel to the incident light were not detected.…”
Section: Resultsmentioning
confidence: 96%
“…An iterative Jones calculus based algorithm was applied to extract the depth-resolved optic axis for mapping the fiber orientation [13]. The fiber orientation measured is between [-90°, 90°] and represents the projected orientations within the plane perpendicular to the incident light [8,14], which is analog to the "helix" angle measured in DTI [2,7]. The system has a 12.4 µm lateral resolution at the focus and a 5.9 µm axial resolution in tissue.…”
Section: Opt Systemmentioning
confidence: 99%
See 1 more Smart Citation